Reducing the burden of hypoglycaemia in people with diabetes through increased understanding: design of the Hypoglycaemia REdefining SOLutions for better liVEs (Hypo‐RESOLVE) project. Issue 6 (5th February 2020) - de Galan, B. E.; McCrimmon, R. J.; Ibberson, M.; Heller, S. R.; Choudhary, P.; Pouwer, F.; Speight, J.; Carlton, J.; Pieber, T. R.; Rosilio, M.; Tack, C. J.; Müllenborn, M.; et al.
Abstract: Background: Hypoglycaemia is the most frequent complication of treatment with insulin or insulin secretagogues in people with diabetes. Severe hypoglycaemia, i.e. an event requiring external help because of cognitive dysfunction, is associated with a higher risk of adverse cardiovascular outcomes and all‐cause mortality, but underlying mechanism(s) are poorly understood. There is also a gap in the understanding of the clinical, psychological and health economic impact of 'non‐severe' hypoglycaemia and the glucose level below which hypoglycaemia causes harm. Aim: To increase understanding of hypoglycaemia by addressing the above issues over a 4‐year period. Methods: Hypo‐RESOLVE is structured across eight work packages, each with a distinct focus. We will construct a large, sustainable database including hypoglycaemia data from >100 clinical trials to examine predictors of hypoglycaemia and establish glucose threshold(s) below which hypoglycaemia constitutes a risk for adverse biomedical and psychological outcomes, and increases healthcare costs. We will also investigate the mechanism(s) underlying the antecedents and consequences of hypoglycaemia, the significance of glucose sensor‐detected hypoglycaemia, the impact of hypoglycaemia in families, and the costs of hypoglycaemia for healthcare systems. Results: The outcomes of Hypo‐RESOLVE will inform evidence‐based definitions regarding the classification of hypoglycaemia in diabetes for use in daily clinical practice, future clinical trials and as a benchmark for comparing glucose‐lowering interventions and strategies across trials. Stakeholders will be engaged to achieve broadly adopted agreement. Conclusion: Hypo‐RESOLVE will advance our understanding and refine the classification of hypoglycaemia, with the ultimate aim being to alleviate the burden and consequences of hypoglycaemia in people with diabetes.